Design, processing and properties of fly ash-based lightweight geopolymer using foaming agent for brick application / \c Wan Mastura binti Wan Ibrahim. - Wan Mastura Wan Ibrahim (School of Materials Engineering, Universiti Malaysia Perlis, 2018)
The aim of this research is to produce fly ash-based lightweight geopolymer for lightweight brick application by using foaming agent through geopolymerization process. The objectives of this study were ; to investigate the effects of sodium hydroxide (NaOH) concentration on fly ash-based lightweight geopolymer based on the compressive strength ; to obtain the optimum foaming agent/water ratio and foam/geopolymer paste ratio on producing fly ash-based lightweight geopolymer based on the compressive strength performance ; to determine the optimum curing temperature and curing time for fly ash-based lightweight geopolymer based on the compressive strength and density analysis ; to analyse the effects of ageing on compressive strength, density and thermal insulation properties of fly ash-based lightweight geopolymer.